2014
DOI: 10.1128/jb.01395-13
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Sequencing of Campylobacter jejuni Insertion Mutant Libraries Reveals mapA as a Fitness Factor for Chicken Colonization

Abstract: bCampylobacter jejuni is a leading cause of gastrointestinal infections worldwide, due primarily to its ability to asymptomatically colonize the gastrointestinal tracts of agriculturally relevant animals, including chickens. Infection often occurs following consumption of meat that was contaminated by C. jejuni during harvest. Because of this, much interest lies in understanding the mechanisms that allow C. jejuni to colonize the chicken gastrointestinal tract. To address this, we generated a C. jejuni transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 27 publications
2
31
2
Order By: Relevance
“…Using a Tn-Seq approach, we previously identified several determinants required by C. jejuni for efficient colonization of the chicken gastrointestinal tract (4). One determinant was a component of the Campylobacter heme utilization gene cluster chuB .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a Tn-Seq approach, we previously identified several determinants required by C. jejuni for efficient colonization of the chicken gastrointestinal tract (4). One determinant was a component of the Campylobacter heme utilization gene cluster chuB .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our group has used both signature-tagged mutagenesis (STM) and insertion sequencing (transposon sequencing [Tn-Seq]) approaches to identify colonization determinants of C. jejuni (4, 5). The earlier STM approach identified genes involved in chemotaxis and flagellar biogenesis, but several other colonization factors were identified using the Tn-Seq approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection of humans often occurs following ingestion of undercooked meat or by consuming uncooked food that has been cross-contaminated. As such, much emphasis has been placed on identifying and characterizing factors of C. jejuni with the goal of using those insights to inform the identification and/or development of strategies or compounds that limit C. jejuni loads in the food supply (2,3). One such factor that has repeatedly been shown to be required for full colonization of the chicken gastrointestinal is the flagella of C. jejuni.…”
Section: Discussionmentioning
confidence: 99%
“…These include signature-tagged mutagenesis and transposon insertion sequencing (Tn-Seq) approaches to identify mutants with decreased cecal abundance; these studies demonstrated that flagella are required for full colonization of the chicken cecum (2,3). Additionally, the regulatory hierarchy of flagellar biosynthesis has been characterized (4).…”
mentioning
confidence: 99%